Morfogénesis in vitro de toona ciliata a partir de raquis de hojas jóvenes con tidiazuron (2005)
The Meliacea are of great importance in construction and furniture-making. Toona ciliata is a Meliacea originally from the Himalayan region; it is known as Himalayan Cedar in Cuba. Natural regeneration occurs in this specie by seed diffusion and grafting; such propagation is limited. The object of this paper was to promote callus formation and plant regeneration in Toona ciliata from in vitro propagation. Two to three year old mature trees (Toona ciliata) were used. Rachis were taken from young branches from these plants. They were disinfected in 0.25% (w/v) mercuric chloride solution for 10 min followed by three rinses in autoclaved distilled-water. They were then established in MS supplemented with 0-1 mg/L thidiazuron culture medium. Nodular calluses were obtained having good morphogenic characteristics. Shoots sprouted from six-month-old calluses in the dark and plant regeneration was done in the light. AIB shoots were rooted in MS medium supplement with 1 mg/L IBA. Key words: callus, Himalayan Cedar, Meliacea, growth regulators, plant regeneration. Abbreviations: IBA- indolebutyric acid, thidiazuron-N-1,2,3-thiadiazol-5-yl-N-phenylurea.